Effects of Lacticaseibacillus paracasei L9 on Oral Microbiota and Cariogenic Factors in Streptococcus mutans-Infected Mice - Xinyao Pu; Bing Fang; Jianmin Wu; Zhi Zhao; Yue Liu; Jingyu Li; Haina Gao; Ran Wang; Ming Zhang (Foods)
In the pathogenesis of dental caries, Streptococcus mutans (S. mutans) plays a central role. S. mutans can produce extracellular polysaccharides, which can help the bacteria form biofilms on the tooth surface, create a stable living environment, and hinder the removal of bacteria by natural defense substances in the oral cavity such as saliva. Meanwhile, the oral microbiota and dietary habits exert long-term influences on its development. This study, employing the BALB/c mouse model, explored the effects of L. paracasei L9 on dental caries. In the experiment, mice underwent the S. mutans inoculation and were subsequently treated with L. paracasei L9 or S. salivarius K12 for 28 consecutive days. The results showed that L. paracasei L9 significantly ameliorated early enamel caries, and both L. paracasei L9 and S. salivarius K12 cooperatively downregulated the expressions of critical cariogenic factors, effectively suppressing the initial adhesion of S. mutans and the formation of dental plaques. L. paracasei L9 reshaped the oral microbiota of caries-affected mice, selectively reducing pathogens abundances and augmenting abundances of probiotics such as Lactobacillaceae and Streptococcus salivarius. This study offers a strategic approach for the management of dental caries, highlighting the potential of these probiotics in the field of oral health.